Adverse Effects Associated with Proton Pump Inhibitor Use - Yibirin, Marcel (Cureus, 2021)
Proton pump inhibitors (PPIs) marked a before and after in the management of gastric acid‐related disorders since their introduction to the market in 1989. Due to a novel, highly effective mechanism of action blocking the last converging step of gastric acid secretion by parietal cells and very few and mostly tolerable side effects, these drugs quickly displaced other pharmacological compounds such as H2 antagonists as the first treatment choice for peptic ulcer disease, gastroesophageal ulcers, Zollinger-Ellison syndrome, nonsteroidal anti-inflammatory drug-associated ulcers, and eradication of Helicobacter pylori, leading to an exponential increase in their prescription up to now. However, widespread PPI use has led to emerging evidence of long-term adverse effects not described previously, including increased risk of kidney, liver, and cardiovascular disease, dementia, enteroendocrine tumors of the gastrointestinal tract, susceptibility to respiratory and gastrointestinal infections, and impaired absorption of nutrients. Although the evidence published thus far has not established strong correlations, it has been relevant enough to raise new questions about PPIs’ safety profile and reconsideration of their clinical indications. Hence, the aim of this review is to evaluate the association between PPI use and the risk of serious adverse effects given increasing concerns about the overuse of PPIs in the general population.